The Sedative Effect of Non-Alcoholic Beer in Healthy Female Nurses - Franco, Lourdes; Sánchez, Cristina; Bravo, Rafael; Rodríguez, Ana B.; Barriga, Carmen; Romero, Eulalia; Cubero, Javier (PLOS ONE, 2012)
Introduction The hop (Humulus lupulus L.), a component of beer, is a sedative plant whose pharmacological activity is principally due to its bitter resins, in particular to the α-acid degradation product 2-methyl-3-buten-2-ol. The mechanism of action of hop resin consists of raising the levels of the neurotransmitter γ-aminobutyric acid (GABA), an inhibitory neurotransmitter acting in the central nervous system (CNS). Objectives To analyze the sedative effect of hops as a component of non-alcoholic beer on the sleep/wake rhythm in a work-stressed population. Methods The experiment was conducted with healthy female nurses (n = 17) working rotating and/or night shifts. Overnight sleep and chronobiological parameters were assessed by actigraphy (Actiwatch®) after moderate ingestion of non-alcoholic beer containing hops (333 ml with 0,0% alcohol) with supper for 14 days (treatment). Data were obtained in comparison with her own control group without consumption of beer during supper. Results Actigraphy results demonstrated improvement of night sleep quality as regards the most important parameters: Sleep Latency diminished (p≤0.05) in the Treatment group (12.01±1.19 min) when compared to the Control group (20.50±4.21 min), as also did Total Activity (p≤0.05; Treatment group = 5284.78±836.99 activity pulses vs Control = 7258.78±898.89 activity pulses). In addition, anxiety as indexed by the State-Trait Anxiety Inventory (STAI) decreased in the Treatment group (State Anxiety 18.09±3.8 vs Control 20.69±2.14). Conclusion The moderate consumption of non-alcoholic beer will favour night-time rest, due in particular to its hop components, in addition to its other confirmed benefits for the organism.